Access to and use of high blood pressure medications in Brazil - Mengue, Sotero Serrate (2016)
OBJECTIVE To analyze the access to and use of medicines for high blood pressure among the Brazilian population according to social and demographic conditions. METHODS Analysis of data from Pesquisa Nacional Sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines), a nationwide cross-sectional, population-based study, with probability sampling, carried out between September 2013 and February 2014 in urban households in the five Brazilian regions. The study evaluated the access and use of medicines to treat people with high blood pressure. The independent variables were gender, age, socioeconomic status and Brazilian region. The study also described the most commonly used drugs and the percentage of people treated with one, two, three or more drugs. Point estimations and confidence intervals were calculated considering the sample weights and sample complex plan. RESULTS Prevalence of high blood pressure was 23.7% (95%CI 22.8–24.6). Regarding people with this condition, 93.8% (95%CI 92.8–94.8) had indication for drug therapy and, of those, 94.6% (95%CI 93.5–95.5) were using the medication at the time of interview. Full access to medicines was 97.9% (95%CI 97.3–98.4); partial access, 1.9% (95%CI 1.4–2.4); and no access, 0.2% (95%CI 0.1–0.4). The medication used to treat high blood pressure, 56.0% (95%CI 52.6–59.2) were obtained from SUS (Brazilian Unified Health System), 16.0% (95%CI 14.3–17.9) from Popular Pharmacy Program, 25.7% (95%CI 23.4–28.2) were paid for by the patients themselves and 2.3% (95%CI 1.8–2.9) were obtained from other locations. The five most commonly used drugs were, in descending order, hydrochlorothiazide, losartan, captopril, enalapril and atenolol. Of the total number of patients on treatment, 36.1% (95%CI 34.1–37.1) were using two medicines and 13.5% (95%CI 12.3–14.9) used three or more. CONCLUSIONS Access to medicines for the treatment of high blood pressure may be considered high and many of them are available free of charge. The most commonly used drugs are among those recommended as first-line treatment for high blood pressure control. The percentage of people using more than one drug seems to follow the behavior observed in other countries.